Sedentary behavior is associated with systemic immune-inflammation index and systemic inflammation response index levels: a cross-sectional analysis of the NHANES 2011–2018 - Wu, Xian; Zhong, Lin; Hu, Yuehong; Ruan, Lingying; Zhou, Kaiyu; Liu, Hanmin; Chen, Lina (Frontiers in Public Health, 2025)
BackgroundSedentary behavior (SB), has been closely linked to numerous detrimental health effects. While the individual and combined impacts of such behaviors on immune-inflammatory responses remain ambiguous, innovative indices like the Systemic Immune-Inflammation Index (SII) and the Systemic Inflammation Response Index (SIRI) are considered as comprehensive tools to assess inflammation. This study endeavors to elucidate the potential correlations between SB, SII, and SIRI, thereby contributing to a deeper understanding of how lifestyle choices influence systemic inflammation profiles.MethodsThis research entailed a retrospective, cross-sectional examination of 39,156 adult participants sourced from 2011 to 2018 of the National Health and Nutrition Examination Survey (NHANES). SASB was used as the independent variable and SII and SIRI as dependent variables. Weighted linear regression was used to assess the correlation between the independent and dependent variables. Smoothed curve fitting and threshold effect analyses were also performed to determine to identify if there was a non-linear relationship between SII and SIRI and SASB. Subgroup analyses were then performed to identify sensitive populations.ResultsA total of 15,789 individuals ≥18 years old were included. Elevated SB levels were correlated with a rise in SII levels in three models (p < 0.05). There was a positive correlation of SB and SII (as a continuous variable). At the same, higher SB was associated with increased SIRI level in three models (p < 0.05). However, there was a non-linear correlation between SB and SIRI with 485 min (min) being the inflection point.ConclusionAmong US adults, SII and SIRI exhibited a positive correlation with heightened SB, underscoring the need for more extensive, prospective studies to further elucidate SB’s impact on these inflammation indices.